2021
DOI: 10.1111/cpr.13136
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SMARCB1 promotes autophagy and facilitates tumour progression in chordoma by transcriptionally activating ATG5

Abstract: Objectives SWI/SNF‐related matrix‐associated actin‐dependent regulator of chromatin subfamily B member 1 (SMARCB1) loss is associated with a poor prognosis in chordoma, while the mechanism remains largely unclear. Here, we aim to explore the function and regulatory mechanisms of SMARCB1 in chordoma. Materials and Methods The effect of SMARCB1 on chordoma cells was investigated in vitro and in vivo. Chromatin immunoprecipitation (ChIP) sequencing was used to investigate the mechanisms of SMARCB1 in chordoma. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Investigators have also recently proposed a novel subtype of chordoma, poorly differentiated chordoma, that shows more aggressive biologic behaviors and poorer survival, and the loss of INI1 is a crucial characteristic of poorly differentiated chordoma (16,17,19). Moreover, our previous study revealed the tumor-suppressive effects of INI1 in chordoma cells, where we found that INI1 inhibited the proliferation and invasion of chordoma cells (20). However, the mechanism underlying INI1's role in chordoma has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Investigators have also recently proposed a novel subtype of chordoma, poorly differentiated chordoma, that shows more aggressive biologic behaviors and poorer survival, and the loss of INI1 is a crucial characteristic of poorly differentiated chordoma (16,17,19). Moreover, our previous study revealed the tumor-suppressive effects of INI1 in chordoma cells, where we found that INI1 inhibited the proliferation and invasion of chordoma cells (20). However, the mechanism underlying INI1's role in chordoma has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 53%
“…While earlier studies were primarily focused on the origin of INI1 loss and the identi cation of locus deletion(16, 19,38), the downstream molecular mechanism underlying INI1 action in chordoma remains almost completely unelucidated. Our previous work suggested that autophagy was involved in the function of INI1, and ATG5 was identi ed as a novel transcriptionalregulation target of INI1; rescue experiments using ATG5 siRNA further con rmed that ATG5-mediated autophagy was critical to the oncogenesis of INI1 loss (20). In this study, we examined another molecular mechanism in which INI1 regulated chordoma progression from the perspective of epigenetics.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…RNF8 promotes proliferation by upregulating c-Myc expression via the Wnt/β-catenin pathway, one of the fundamental signaling cascades in development and homeostasis (51). SWI/SNF-related matrix-associated actin-dependent regulator of chromatin subfamily B member 1 ( SMARCB1 ) is a tumor suppressor which regulates ATG5, an essential autophagy-related gene that plays a vital role in autophagosome formation (52). During preadipocyte proliferation and differentiation, FoxO6 directly targets and induces expression of cyclin G2 ( CCNG2 ) (53).…”
Section: Discussionmentioning
confidence: 99%
“…While some of the TFs picked up in this study that are known interacting partners of FOS, is a tumor suppressor which regulates ATG5, an essential autophagy-related gene that plays a vital role in autophagosome formation (52). During preadipocyte proliferation and differentiation, FoxO6 directly targets and induces expression of cyclin G2 (CCNG2) (53).…”
Section: Transcription Factor Expression Profilementioning
confidence: 99%